Controls on Dissolved Silicon Isotopes Along the U.S. GEOTRACES Eastern Pacific Zonal Transect (GP16). Issue 9 (28th August 2020) - Grasse, P.; Closset, I.; Jones, J. L.; Geilert, S.; Brzezinski, M. A.
Abstract: The distribution of dissolved silicon isotopes (δ 30 Si) was examined along the U.S. GEOTRACES East Pacific Zonal Transect (GP16) extending from Peru to Tahiti (10°S and 15°S latitude). Surface waters in the subtropical gyre displayed high δ 30 Si due to strong utilization of silicic acid (DSi). In contrast, surface waters close to the Peruvian coast where upwelling prevailed were less depleted and only moderately fractionated. δ 30 Si of water masses along the transect was compared with the results of an Optimum Multiparameter Analysis that quantified the fractional contributions of end‐member water masses in each sample. Strong admixture of intermediate waters obscured the expected heavy isotopic signatures of Subantarctic Mode Water and Antarctic Intermediate Water. Isotope values were nearly homogenous below 2, 000 m (average: +1.3 ± 0.1‰, 1 s.d.) despite the 25 μmol kg −1 range in the DSi content among water masses. This homogeneity confirms prior observations and model results that predict nearly constant δ 30 Si values of +1.0‰ to +1.2‰ for Pacific deep waters with [DSi] > 100 μmol kg −1 . Waters above the East Pacific Rise (EPR) influenced by hydrothermal activity showed a small increase in [DSi] together with dissolved iron, but overall stations close to the EPR were slightly depleted in [DSi] (3 to 6 μmol kg −1 ) with no significant shift in δ 30 Si compared to adjacent waters. Hydrothermal [DSi] appears to precipitate within the conduit of the EPR or upon contact with cold seawater resulting in a negligible influence of hydrothermal fluids on δ 30 Si in deep water. Key Points: Surface waters have a large range in dissolved silicon isotopes covering nutrient‐rich coastal upwelling to oligotrophic waters Deep water masses with DSi concentrations >100 μmol kg −1 show homogenous silicon isotope signatures despite up to 25 μmol kg −1 differences in [DSi] Hydrothermal fluids have a negligible effect on Si isotope distributions in the deep Pacific